Targeting Detoxifying Enzymes in the Lymphatic Filariasis Vector: An In Silico Study on Curcumin, Camphor, and Menthol - Subahar, Rizal; Winita, Rawina; Dwira, Surya; El Bayani, Gulshan Fahmi (UI Scholars Hub, 2025)
Vector control remains a critical component in the prevention of lymphatic filariasis, a disease transmitted by insect vectors. Natural compounds such as curcumin, camphor, and menthol are being explored for their bio-insecticidal properties due to their potential to inhibit key detoxification and neurological enzymes in insects, including acetylcholinesterase (AChE), glutathione S-transferase (GST), and cytochrome P450 oxidases (CYP450). A molecular docking study using SwissDock was conducted to evaluate the interaction of curcumin, camphor, and menthol with AChE, GST, and CYP450 enzymes. Binding affinity (ΔG), hydrogen bonding, and active site interactions were analyzed to assess the inhibitory potential of each compound. Curcumin showed the highest binding affinity across all target enzymes. AChE (-8.2 kcal/mol), GST (-7.9 kcal/mol), and CYP450 (-7.5 kcal/mol). It formed strong hydrogen bonds with key catalytic residues, suggesting effective inhibition of neurotoxicity and detoxification pathways. Camphor displayed moderate binding affinities with AChE (-7.1 kcal/mol), GST (-6.5 kcal/mol), and CYP450 (-7.2 kcal/mol), primarily through hydrophobic interactions. Menthol exhibited the weakest binding, with limited hydrogen bonding and lower affinities (AChE: -6.4 kcal/mol, GST:-5.9 kcal/mol, CYP450: -6.3 kcal/mol). The findings suggest that curcumin is a promising candidate for insect vector control through inhibition of critical enzyme systems involved in neurotransmission and detoxification. Camphor may offer moderate bioactivity, while menthol appears less potent. These insights support further exploration of phenolic compounds as environmentally friendly, natural insecticidal agents against vectors of lymphatic filariasis.